CONVERSATION ANALYSIS: TURN TAKING ON INDONESIA LAWYER CLUB TALK SHOW - Putu Pande Novita Sari; Ni Luh Putu Sri Adnyani; I Made Suta Paramarta (Lingua Scientia, 2021)
This present study aims at analyzing the turn-taking strategy in a debate of Sunda Empire in Indonesia Lawyer Club (ILC) talk show broadcasted by TV One, one of the national television channels in Indonesia. Sunda Empire is an organization whose foundation lies in the romanticized idea of reviving glorious feudal kingdom of Sunda.  With the application of the turn-taking strategy by Stenstroom's framework, this qualitative study was conducted through conversational analysis. There were five steps in analyzing the conversation, such as streaming Indonesia lawyer club episode Sunda Empire, taking note of the conversation, classifying the data, transcribing the data, translating the data, and interpreting the data. The results of the study revealed that all turn-taking strategies appear in the debate namely starting up, taking over, interrupting, overlapping, repair, silent pause, repeating words, filled pause, promoting, appealing, and giving up strategy. The most frequent turn-taking strategy occurred is starting up strategy. Theoretically, this study can support the theory of conversational analysis of turn-taking strategy. Practically, teachers can use it as a reference for an applied linguistics course.